Manchester Screening System: difficulties faced by nurses in risk classification (Research, Society and Development, 2022)
Objective: To carry out an integrative literature review to identify and describe the difficulties faced by nurses in risk classification (Manchester Screening System) in emergency care units. Method: Integrative Literature Review with search for scientific articles in LILACS, BDENF and ColecionaSUS databases with the following descriptors combined with the Boolean operator AND: "Emergency nursing" AND "Triage" AND "Welcoming". Articles published from 2016 to 2021, in Portuguese, were included, as well as full text articles with online access. Studies in other languages, duplicates, theses, dissertations, monographs and integrative reviews were excluded, as well as texts that did not answer the guiding question: “What are the difficulties faced by nurses in classifying the risk of patients in urgent and emergency care?”. Results: A total of 63 studies were identified, with 42 studies being excluded after the adoption of the inclusion and exclusion criteria. After reading the entire 23 remaining articles, 16 articles were excluded, as they did not answer the guiding question. Thus, five articles remained as the final sample. After analyzing the studies, two categories were listed, namely: Welcoming with Risk Classification: barriers to consolidating the autonomy of nurses; and Workload and risk rating: obstacles to a reliable assessment. Final considerations: this study had as its central theme to identify and describe the difficulties faced by nurses in risk classification, through the Manchester Triage System protocol, in Urgency and Emergency units.